The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1519-69842013000200014
|View full text |Cite
|
Sign up to set email alerts
|

The orchid-bee fauna (Hymenoptera: Apidae) of ‘Reserva Biológica de Una’, a hotspot in the Atlantic Forest of southern Bahia, eastern Brazil

A Nemésio

Abstract: The orchid-bee fauna of 'Reserva Biológica de Una' (REBIO Una), one of the largest Atlantic Forest remnants in southern Bahia, eastern Brazil, was surveyed for the first time. Baits with sixteen different scents were used to attract males of orchid bees. Eight hundred and fifty-nine males belonging to 26 species were actively collected with insect nets during 60 hours in January and February, 2009, and January, 2010. Euglossa avicula Dressler, 1982 and Euglossa milenae Bembé, 2007 have been recorded for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(10 reference statements)
1
10
0
1
Order By: Relevance
“…Euglossa amazonica, E. clausi, and E. imperialis were not recorded in the DLOF. In spite of being recorded in the other three areas, E. amazonica was not an abundant species, as other authors have already pointed out (Nemésio, 2011b(Nemésio, , 2013aPires et al, 2013, mentioned as Euglossa aratingae Nemésio). According to Nemésio (2009), this species has a broad distribution, but it is rarely sampled.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Euglossa amazonica, E. clausi, and E. imperialis were not recorded in the DLOF. In spite of being recorded in the other three areas, E. amazonica was not an abundant species, as other authors have already pointed out (Nemésio, 2011b(Nemésio, , 2013aPires et al, 2013, mentioned as Euglossa aratingae Nemésio). According to Nemésio (2009), this species has a broad distribution, but it is rarely sampled.…”
Section: Discussionmentioning
confidence: 58%
“…Studies carried out in other Atlantic forest areas also pointed out to the dominance of this species (Aguiar & Gaglianone, 2008Ramalho et al, 2009;Ramalho et al, 2013;Nemésio, 2013aNemésio, , 2013b. Euglossa cordata has been frequently considered a bioindicator of environmental disturbances, as this species if favored by dry and/or perturbed environments (Peruquetti et al, 1999;Silva & Rebelo, 2002;Aguiar & Gaglianone, 2008;Rocha-Filho & Garófalo, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roubik (2004a) had already suggested that surveys of orchid-bee males with scent baits during a single day have great utility, and may reveal almost as much about local community structure as studies lasting a full year. The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b).…”
Section: Sampling Protocolmentioning
confidence: 90%